2022
DOI: 10.1371/journal.pgen.1009937
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplastin genetically interacts with Cadherin 23 and the encoded isoform Np55 is sufficient for cochlear hair cell function and hearing

Abstract: Mammalian hearing involves the mechanoelectrical transduction (MET) of sound-induced fluid waves in the cochlea. Essential to this process are the specialised sensory cochlear cells, the inner (IHCs) and outer hair cells (OHCs). While genetic hearing loss is highly heterogeneous, understanding the requirement of each gene will lead to a better understanding of the molecular basis of hearing and also to therapeutic opportunities for deafness. The Neuroplastin (Nptn) gene, which encodes two protein isoforms Np55… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…Cdh23 c.753A>G ), we recently demonstrated that the closely related gene Neuroplastin genetically interacts with the Cdh23 ahl allele potentiating the auditory deficit exhibited by Neuroplastin mutant mice. 7 Here, we demonstrate that Embigin also genetically interacts with the Cdh23 ahl allele, causing high-frequency hearing deficits from as early as 1-month of age. However, unlike in the case of Neuroplastin , the cause of hearing impairment in the Embigin mutant is not due to a physical interaction with plasma membrane calcium ATPase (PMCA) proteins.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Cdh23 c.753A>G ), we recently demonstrated that the closely related gene Neuroplastin genetically interacts with the Cdh23 ahl allele potentiating the auditory deficit exhibited by Neuroplastin mutant mice. 7 Here, we demonstrate that Embigin also genetically interacts with the Cdh23 ahl allele, causing high-frequency hearing deficits from as early as 1-month of age. However, unlike in the case of Neuroplastin , the cause of hearing impairment in the Embigin mutant is not due to a physical interaction with plasma membrane calcium ATPase (PMCA) proteins.…”
Section: Introductionmentioning
confidence: 62%
“…Furthermore, histological sections prepared from 24-week old Emb +/+ and Emb tm1b/tm1b mice maintained on a C57BL/6N background showed normal cochlear morphology in the Emb tm1b/tm1b cochleae, with no evidence for loss or degeneration of: hair cells; spiral ganglion neurons; stria vascularis or supporting cells ( Figure 4 A). Given that we have recently reported significant IHC synaptic deficits in the Embigin-related Neuroplastin null mice, 7 synaptic coupling between IHCs and afferent terminals of spiral ganglion neurons in Emb tm1b mice maintained on a C57BL/6N background was assessed by whole-mount immuno-labeling. 5 , 7 Co-labeling with anti-Ribeye (pre-synaptic ribbon marker) and anti-GluR2 (post-synaptic density marker) revealed no evidence of a synaptic deficit with similar numbers of matched, unmatched, and total number of puncta per IHC observed in Emb tm1b/tm1b mice as compared to wild type littermates at 6-week of age ( Figures 4 B and 4C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CAMs act to bridge pre- and post-synaptic domains to initiate, maintain and specify synapses (reviewed in: (Südhof, 2021)). Work in mouse auditory inner hair cells (IHCs) has implicated the CAM Neuroplastin (Np55/Np65) and the neuronal CAM (NrCAM) in the development of IHC ribbon synapses (Carrott et al, 2016; Harley et al, 2018; Newton et al, 2022). More recent work in mouse found that a well-studied family of postsynaptic CAMs, neuroligins (Nlgns), are important for ribbon-synapse assembly (Ramirez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%